STUDI KASUS: DAMPAK KEHAMILAN REMAJA TERHADAP PERAWATAN KEHAMILAN DAN BAYI - Achmad, Ismiyanti; Hitipeuw, Antonetha (Poltekkes Kemenkes Maluku, 2024)
Teenage pregnancy is a significant public health problem and has a broad impact on the health of mothers and babies. This case study describes the pregnancy of a 19 year old teenager (Mrs. M), which shows the various challenges faced in pregnancy care and baby health. This case shows that teenage pregnancies are often faced with inadequate antenatal care, higher risks to maternal and infant health, and an urgent need for comprehensive psychosocial and educational support. The midwifery care provided can provide motivation for mothers to get access and quality pregnancy checks, can also reduce the social and psychological impacts experienced, as well as support for pregnancy